Teaching Methods, Challenges, And Strategies For Improving Students' Arabic Linguistic Competence - Husein, Sudi Yahya; Hasaniyah, Nur; Murdiono, Murdiono; Akmaluddin, Akmaluddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Linguistic competency improvement strategies need to be developed to face challenges. This study aims to analyze Arabic language learning in Islamic universities in Indonesia, focusing on teaching methods, challenges faced, and strategies to improve students' linguistic competence. This study uses a qualitative approach by collecting data through classroom observation, interviews with Arabic teachers, and analysis of related documents in Indonesian Islamic University (UII), State Islamic University (UIN) Jakarta, State Islamic University (UIN) Yogyakarta, State Islamic University (UIN) Sunan Kalijaga, State University of Malang (UM), Yogyakarta State University (UNY). The results showed that the teaching methods commonly used in Islamic universities in Indonesia are lecture methods, discussion methods, demonstration methods, and problem-solving methods. However, the use of the lecture method is still dominant in the context of Arabic language learning. Challenges faced by students in learning Arabic include the complexity of Arabic grammar, time constraints, lack of resources, and a dense curriculum. Strategies identified include using educational technology in Arabic language learning, teacher training and mentorship, extracurricular programs involving the Arabic language, and an emphasis on developing speaking and writing skills in Arabic.